Proceedings of the 1st International Conference on Education Social Sciences and Humanities (ICESSHum 2019) 2019
DOI: 10.2991/icesshum-19.2019.103
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Instagram to Increase Students’ Motivation and Students’ Competence in Learning English

Abstract: Social media is a part of modern people lifestyle in Industrial Revolution 4.0. Furthermore, it has started to be utilized in education field as one of the learning media, for example, Instagram. It is widely known among social media users. Several studies have proved positive impacts on the use of social media in developing students' English skills. However, the studies about Instagram, specifically in relation to English lesson at schools are limited. Thus, using a case study method, this study is conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
0
22
0
2
Order By: Relevance
“…• el uso de los dispositivos móviles mediante la utilización de las redes sociales, más concretamente una de las más famosas y utilizadas entre los adolescentes en la actualidad como es Instagram (Pujiati, Zahra y Tamela, 2019; We are social, 2020).…”
Section: Uniendo De Forma Combinada Diversas Variables Como Sonunclassified
“…• el uso de los dispositivos móviles mediante la utilización de las redes sociales, más concretamente una de las más famosas y utilizadas entre los adolescentes en la actualidad como es Instagram (Pujiati, Zahra y Tamela, 2019; We are social, 2020).…”
Section: Uniendo De Forma Combinada Diversas Variables Como Sonunclassified
“…It is through communication that man begins to realise his potential and acquire or renew skills that allow greater and better action and interaction with the social world in which he is inserted (Aloraini, 2018). All transmission of knowledge, technological or not, happens through one form or another of teaching and this presupposes some type of communication, which must reflect an organised system that allows learning (Pujiati and Tamela, 2019). As learning something new, generally, presupposes the acquisition of new information, effective teaching cannot be considered that way, unless communication is also so.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…According to a study by Aloraini, (2018) access to reading is part of social rights and plays an important role in the exercise of citizenship. Therefore, its relevance expands and integrates knowledge, opening more and more horizons of knowledge, enriching vocabulary and ease of communication, disciplining the mind and broadening consciousness (Pujiati and Tamela, 2019). The profile of the students has undergone major changes, especially in relation to the written material.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies projected the supremacy and effectiveness of Instagram in learning. For example, the study of Pujiati, Zahra, and Tamela (2019) examined the use of Instagram to increase students' motivation of learning English language. Likewise, Yadegarfar and Simin (2016) investigated the efficacy of Instagram on learning grammatical structures in Iranian undergraduate and the study revealed that learning with Instagram was positive.…”
mentioning
confidence: 99%